Ultrathin micro battery device of transmission electron microscope capable of using organic electrolyte and assembly method
By designing an ultra-thin micro battery device and using an ultra-thin conductive film to clamp the organic electrolyte, the problem of resolution degradation in transmission electron microscope is solved, and the observation and failure mechanism of battery materials at the atomic scale is realized, and the actual battery environment is simulated.
Patent Information
- Application Number
- CN202510432079.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-07-08
AI Technical Summary
Existing transmission electron microscope microbattery devices cannot use highly volatile organic electrolytes, resulting in the degradation of the electron microscope resolution, unable to simulate the working environment of the actual battery, and unable to obtain electrochemical information at the atomic scale.
An ultra-thin micro battery device is designed, using two layers of ultra-thin conductive films to clamp the organic electrolyte, including a negative electrode sheet, a separator, a first ultra-thin conductive film, an organic electrolyte and a positive electrode particles, a second ultra-thin conductive film and a positive electrode sheet. The overall thickness is less than 30nm, and it is suitable for transmission electron microscope sample rods to achieve atomic resolution observation.
It realizes the use of organic electrolyte in transmission electron microscopes to simulate the actual battery environment, can observe the structural changes of battery materials at the atomic scale, conduct in-depth research on the failure mechanism, and reduce the risk of electron microscope damage.
Smart Images

Figure CN120280565A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the fields of material research and electron microscopy, and relates to a micro-battery device for a transmission electron microscope that can use an organic electrolyte and an assembly method thereof. Background Art
[0002] In-situ transmission electron microscopy (In-situ TEM) technology has become a very important characterization means for scientific researchers to analyze the battery structure because it can observe the structural dynamic change process of electrode materials during battery operation in real time and obtain surface structure information at the atomic level. The in-situ transmission electron microscopy micro-battery device developed nowadays can be encapsulated according to an assembly method close to that of an actual battery (Zhang Wei, Huang Xue, Tian Jing. Chinese Patent CN 115020847B). However, this assembly method can only use low-volatility ionic liquids as electrolytes. If a highly volatile organic electrolyte used in commercial lithium batteries is adopted, it will cause rapid volatilization of the electrolyte during the experiment. Although a closed space can be realized by manufacturing an observation window with a double-layer SiN x to encapsulate a commercial organic electrolyte, the scattering effect of the SiN x film (>50 nm) and the liquid in the sample cell (>150 nm) on electrons is serious, which degrades the resolution of the electron microscope from the atomic scale (>0.07 nm) to above 1 nm, unable to meet the requirements of atomic-scale analysis. In addition, the in-situ micro-battery device based on the SiN x film usually cannot obtain normal charge-discharge curves, so it cannot simulate the actual working environment of the battery.
[0003] In summary, there is an urgent need to develop an ultra-thin micro-battery device for a transmission electron microscope that can achieve atomic resolution, can reproduce the true electrochemical working curve of an actual battery, and can be used to explore the transformation mechanism of the microscopic structure during the charge and discharge process of an actual lithium battery. Summary of the Invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an ultra-thin micro-battery device for a transmission electron microscope that can use an organic electrolyte and an assembly method thereof, which can realize in-situ observation of battery materials at the atomic scale in a transmission electron microscope, enabling researchers to observe the microscopic structure evolution of battery materials in real time under real charge and discharge conditions through the action of an electric field and a liquid environment, so as to deeply study its failure mechanism and reaction mechanism.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0006] The first aspect of the present invention is to provide an ultra-thin micro-battery device for a transmission electron microscope that can use an organic electrolyte, including a negative electrode plate, a separator, a first ultra-thin conductive film, a second ultra-thin conductive film, and a positive electrode plate arranged in sequence. Positive electrode particles and an organic electrolyte are encapsulated between the first ultra-thin conductive film and the second ultra-thin conductive film. Through holes are formed in the centers of the negative electrode plate, the separator, and the positive electrode plate and are coaxial.
[0007] Further, the positive electrode particles are one or more of graphite, layered structure materials, lithium iron phosphate, and lithium manganate.
[0008] Further, the separator is a glass fiber separator, which is an isolation film used in batteries and is usually composed of materials such as cellulose and glass fiber.
[0009] Further, the first ultra-thin conductive film and the second ultra-thin conductive film are made of the same material, both being a conductive carbon film or a graphene film.
[0010] Further, the total thickness of the first ultra-thin conductive film and the second ultra-thin conductive film is less than 20 nm, and the overall thickness of the ultra-thin micro-battery device is 0.8 - 1.2 mm, preferably 1 mm, which can meet the space requirements of different types of transmission electron microscope pole shoes, can be adapted to various types of in-situ sample holders, meets the TEM imaging standard, can truly simulate the working environment of commercial batteries, and can also reduce the risk of damage to the transmission electron microscope during the experiment.
[0011] Further, the through-hole diameters of the negative electrode plate and the positive electrode plate are the same, the through-hole diameter of the separator is smaller than the through-hole diameters of the negative electrode plate and the positive electrode plate, and the diameters of the first ultra-thin conductive film and the second ultra-thin conductive film are the same and larger than the through-hole diameters of the negative electrode plate and the positive electrode plate. In actual applications, it can be slightly adjusted according to the size of the sample holder head.
[0012] Further, the area ratio of the separator to the negative electrode plate is 1.5:1.
[0013] Preferably, the negative electrode plate is square, 5 mm long and 4 mm wide, with a hole punched in the center of the electrode plate, and the hole diameter is 1.0 mm; the separator is square, 6 mm long and 5 mm wide, with a hole punched in the center of the separator, and the hole diameter is 0.8 mm; the positive electrode plate is square, 5 mm long and 4 mm wide. A hole is punched in the center of the electrode plate, and the hole diameter is 1.0 mm.
[0014] Further, the negative electrode plate is made by dispersing a negative electrode active material, a conductive agent, and a binder in a solvent in a mass ratio of 8:1:1, then coating it into a 180 - 220 μm electrode plate, drying it in vacuum, and then cutting it into pieces. Or directly use a lithium metal sheet.
[0015] Further, the positive electrode sheet is prepared by dispersing a positive electrode active material, a conductive agent, and a binder in a mass ratio of 8:1:1 in a solvent, then coating the sheet to a thickness of 180 - 220 μm, drying it under vacuum, and then cutting it into pieces.
[0016] Among them, the negative electrode active material is one or more of lithium metal, lithium-containing alloy, and lithium titanate; the conductive agent is one or more of conductive carbon, carbon nanotubes, and amorphous carbon;
[0017] The positive electrode active material is one or more of graphite, layered structure material, lithium iron phosphate, and lithium manganate; the conductive agent is one or more of conductive carbon, carbon nanotubes, and amorphous carbon;
[0018] The binder is one or more of PVDF, styrene-butadiene rubber, and sodium carboxymethyl cellulose; the solvent is N-methylpyrrolidone.
[0019] Further, the separator is infiltrated with an ionic liquid and pressed with a glass slide until there are no obvious liquid traces.
[0020] The second aspect of the present invention provides an assembly method for an ultra-thin micro-battery device of a transmission electron microscope that can use an organic electrolyte. In a drying chamber or a vacuum glove box (usually a low-humidity environment), first, a second ultra-thin conductive film is placed in the center of the positive electrode sheet. Then, the positive electrode particles are dispersed with ethanol and dropped onto the second ultra-thin conductive film. After drying, an organic electrolyte is dropped onto the second ultra-thin conductive film. Then, a first ultra-thin conductive film is covered on the positive electrode particles and the organic electrolyte, a separator is covered on the first ultra-thin conductive film, and a negative electrode sheet is covered on the separator to encapsulate a micro-battery. The micro-battery is installed on a sample rod, and then the sample rod is inserted into the transmission electron microscope. The rear section of the sample rod has an electrical interface connected to an electrochemical workstation. The electrochemical workstation can provide corresponding electrochemical charge and discharge tests. Thus, by applying the transmission electron microscope, the structural changes of battery materials under the conditions of an electric field and an organic electrolyte can be studied, the failure mechanism of battery materials can be explored, and new methods and ideas can be provided for optimizing battery materials.
[0021] Further, the environment for dropping is a dew point of -40 °C, a temperature of 20 °C, the drying time is 40 - 60 min, and the addition amount of the organic electrolyte is 30 μL.
[0022] Advantages and beneficial effects of the present invention:
[0023] 1. The present invention encapsulates a negative electrode plate, a separator, a first ultra-thin conductive film, an organic electrolyte, positive electrode particles, a second ultra-thin conductive film, and a positive electrode plate into an ultra-thin micro-battery (the thickness of the observation window < 30 nm). This battery can be installed on the sample holder of a transmission electron microscope, enabling atomic resolution of the electron microscope, capable of reproducing the true electrochemical working curve of an actual battery. Based on the atomic scale, it can explore the transformation mechanism of the micro-structure of the battery under working conditions.
[0024] 2. For the first time under the condition of a non-SiNx window, an organic electrolyte is used in the assembly of the micro-battery in the present invention. By sandwiching the organic electrolyte with two ultra-thin conductive films, the problem of strong volatility of the organic electrolyte is solved, enabling the effective simulation of the actual working environment of commercial lithium batteries in a transmission electron microscope. This design breaks through the traditional limitation of only using ionic liquids, making the in-situ research of battery materials closer to the actual battery working conditions.
[0025] 3. High-precision in-situ research tool: The micro-battery device sandwiches the electrolyte with ultra-thin conductive films, which not only effectively inhibits the volatilization of the organic electrolyte but also ensures the atomic resolution of the electron microscope during in-situ observation. This design enables researchers to observe the structural changes of battery materials at the atomic scale under real charge and discharge conditions, deeply explore the material failure mechanism, and provide new research means and directions for optimizing battery performance.
[0026] 4. Structural innovation and material adaptability: The overall thickness of the micro-battery device of the present invention is 1 mm, which can meet the space requirements of different types of pole shoes of transmission electron microscopes and is adaptable to various types of in-situ sample holders. At the same time, the negative electrode plate, the positive electrode plate, and the separator are all designed as perforated square structures, effectively supporting good imaging effects in a transmission electron microscope and capable of truly simulating the charge and discharge process of the battery.
[0027] 5. Personalized and reusable assembly method: The assembly method of the present invention meets the requirements of different models of transmission electron microscopes, and the encapsulation process is simple. All external components can be reused, greatly reducing the experimental cost and operation complexity. At the same time, the design of wrapping the electrolyte with a conductive film ensures stable imaging and reaction analysis at the atomic scale. Brief Description of the Drawings
[0028] Figure 1 is an exploded view of the ultra-thin micro-battery device of the present invention;
[0029] Figure 2 is a schematic operation diagram of dropping positive electrode particles and an organic electrolyte between the first ultra-thin conductive film and the second ultra-thin conductive film.
[0030] Figure 3 is a comparison chart of the charge and discharge curves of a button battery (left) and the ultra-thin micro-battery device of the present invention (right);
[0031] In the figure: 1 - negative electrode plate; 2 - separator; 3 - first ultra-thin conductive film; 4 - second ultra-thin conductive film; 5 - positive electrode plate. Specific embodiments
[0032] The present invention will be further described in detail below through specific embodiments. The following embodiments are only descriptive and not restrictive, and the protection scope of the present invention cannot be limited thereby.
[0033] The present invention can use a micro-battery device of a transmission electron microscope with an organic electrolyte, such as Figure 1 As shown, it includes a negative electrode plate 1, a separator 2, a first ultra-thin conductive film 3, a second ultra-thin conductive film 4, and a positive electrode plate 5. On the second ultra-thin conductive film 4 are positive electrode particles and an organic electrolyte.
[0034] Both the first ultra-thin conductive film 3 and the second ultra-thin conductive film 4 are made of conductive carbon film. The positive electrode particles are made of graphite flakes, and the organic electrolyte is DMC:EC:EMC (volume ratio 2:1:2) containing 1M LiPF6
[0035] The preparation method of the positive electrode plate 5 is as follows: The positive electrode active material graphite flakes, the conductive agent conductive carbon, and the binder PVDF are dispersed in N-methylpyrrolidone in a ratio of 8:1:1. Then it is coated into a 200-μm electrode plate, dried in a vacuum drying oven, and then cut into pieces to be used as the positive electrode plate. It is cut into a size of 5 mm in length and 4 mm in width. A hole is punched in the center of the electrode plate, and the pore diameter is 1.0 mm.
[0036] The preparation method of the negative electrode plate 1 is as follows: The negative electrode active material lithium metal sheet is made into a 200-μm electrode plate to be used as the negative electrode plate. It is cut into a size of 5 mm in length and 4 mm in width. A hole is punched in the center of the electrode plate, and the pore diameter is 1.0 mm.
[0037] The separator 2 is made of glass fiber, 6 mm in length, 5 mm in width, with a hole punched in the center, and the pore diameter is 0.8 mm. Then the separator is infiltrated with an ionic liquid, pressed with a glass slide until there is no obvious liquid trace, and placed on the ultra-thin conductive film.
[0038] The assembly method of this ultra-thin micro-battery device is as follows:
[0039] In a drying chamber or a vacuum glove box, first, place the second ultra-thin conductive film 4 in the center of the positive electrode plate 5, and then disperse the positive electrode particles with ethanol and drop them onto the second ultra-thin conductive film 4. After drying for 50 min, drop 30 μL of the organic electrolyte onto the second ultra-thin conductive film 4. The dropping environment is a dew point of -40°C and a temperature of 20°C, such as Figure 2As shown, a first ultra-thin conductive film 3 is then covered on the positive electrode particles and the organic electrolyte, a separator 2 is covered on the first ultra-thin conductive film, a negative electrode sheet 1 is covered on the separator, and a micro-battery is encapsulated; the micro-battery is installed on a sample rod, and then the sample rod is inserted into a transmission electron microscope. There is an electrical interface at the rear section of the sample rod, which is connected to an electrochemical workstation. The electron beam is turned on, the appropriate magnification is adjusted, the sample area to be observed is found, the parameters of the electrochemical workstation are set, and in-situ electrical experiments are carried out to obtain relevant pictures.
[0040] The same positive electrode sheet 5, negative electrode sheet 1, separator 2, and electrolyte (DMC: EC: EMC containing 1 M LiPF6) as the above ultra-thin micro-battery device are assembled into a button battery, and a constant current charge-discharge test is carried out at a rate of 0.6C.
[0041] Figure 3 Figure for comparing the charge-discharge curves of the button battery (left) and the ultra-thin micro-battery device of the present invention (right). From Figure 3 It can be seen that the micro-battery device can obtain an electrochemical working curve consistent with that of an actual battery, so the real electrochemical reaction process inside the actual battery can be simulated.
[0042] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the inventive concept, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention.
Claims
1. An ultra-thin micro-battery device for a transmission electron microscope that can use an organic electrolyte, characterized in that, It includes a negative electrode plate, a separator, a first ultra-thin conductive film, a second ultra-thin conductive film, and a positive electrode plate arranged in sequence. Positive electrode particles and an organic electrolyte are encapsulated between the first ultra-thin conductive film and the second ultra-thin conductive film. Through holes are made in the centers of the negative electrode plate, the separator, and the positive electrode plate and are coaxial.
2. The ultra-thin micro-battery device of a transmission electron microscope capable of using an organic electrolyte according to claim 1, characterized in that, The total thickness of the first ultra-thin conductive film and the second ultra-thin conductive film is less than 20 nm, and the overall thickness of the ultra-thin micro-battery device is 0.8 - 1.2 mm.
3. The ultra-thin micro-battery device for a transmission electron microscope using an organic electrolyte according to claim 1, characterized in that, The through-hole diameters of the negative electrode plate and the positive electrode plate are the same. The through-hole diameter of the separator is smaller than those of the negative electrode plate and the positive electrode plate. The diameters of the first ultra-thin conductive film and the second ultra-thin conductive film are the same and larger than the through-hole diameters of the negative electrode plate and the positive electrode plate.
4. The ultra-thin micro-battery device for a transmission electron microscope capable of using an organic electrolyte according to claim 1, characterized in that The area ratio of the separator to the negative electrode plate is 1.5:
1.
5. The ultra-thin micro-battery device for a transmission electron microscope capable of using an organic electrolyte according to claim 1, characterized in that, The negative electrode plate is made by dispersing a negative electrode active material, a conductive agent, and a binder in a solvent at a mass ratio of 8:1:1, then coating it into a pole piece with a thickness of 180 - 220 μm, drying it in vacuum, and then cutting it into pieces.
6. The ultra-thin micro-battery device for a transmission electron microscope capable of using an organic electrolyte according to claim 1, characterized in that, The positive electrode plate is made by dispersing a positive electrode active material, a conductive agent, and a binder in a solvent at a mass ratio of 8:1:1, then coating it into a pole piece with a thickness of 180 - 220 μm, drying it in vacuum, and then cutting it into pieces.
7. The ultra-thin micro-battery device for a transmission electron microscope using an organic electrolyte according to claim 1, characterized in that, The separator is infiltrated with an ionic liquid and pressed with a glass slide until there are no obvious liquid traces.
8. The assembling method of the ultra-thin micro-battery device of the transmission electron microscope capable of using an organic electrolyte according to any one of claims 1-7, characterized in that, In a drying chamber or a glove box under vacuum, first, place the second ultra-thin conductive film in the center of the positive electrode plate. Then, disperse the positive electrode particles with ethanol and drop them onto the second ultra-thin conductive film. After drying, drop the organic electrolyte onto the second ultra-thin conductive film. Then, cover the positive electrode particles and the organic electrolyte with the first ultra-thin conductive film, cover the first ultra-thin conductive film with the separator, and cover the separator with the negative electrode plate to encapsulate a micro-battery. Install the micro-battery on a sample rod, then insert the sample rod into a transmission electron microscope. There is an electrical interface at the rear section of the sample rod, which is connected to an electrochemical workstation.
9. The assembly method according to claim 8, wherein, The environment for dropping is a dew point of -40°C and a temperature of 20°C, and the drying time is 40 - 60 min.
Citation Information
Patent Citations
A microbattery structure for transmission electron microscope sample holder based on battery material research
CN115020847B